HUKUM MEDIA MASSA DAN REGULASI MEMANDANG KEDAULATAN RAKYAT DALAM UNDANG-UNDANG PILKADA - Muhamad Zainuri (Jurnal Dakwah dan Komunikasi, 2022)
Elections are always used as an excuse to uphold people's sovereignty, but the election regulations themselves are not in accordance with the will of the people because they make it difficult for the people themselves. Branston and Stafford's (2003: 90-106) approach will be used to further explore how mass media law theory and regulation relate to various questions such as issues around deregulation and liberalization, the realm of contemporary policymakers, and finally about free markets. The results show that election laws tend to be more based on the interests of politicians, and the people can only be spectators of a power that cannot be contested. Even though the election law is very good, there are still gaps for certain individuals to undermine the functioning of democracy in Indonesia.